Molecular Mechanisms of Vitamin D-Mediated Immunomodulation: - Shah, Syed Imran Ali; Alswailmi, Farhan Khashim; Nawaz, Haleema; Al-Mazaideh, Ghassab Mohammad (Galen Medical Journal, 2021)
Ever since discovering the fat-soluble secosteroid vitamin D, an abundance of research has been conducted on the molecular mechanisms for the multiple health benefits of this nutrient. Studies on the beneficial effects of vitamin D supplementation have found appreciable evidence suggesting that it may play a more prime role than initially presumed. Though it has largely been implicated in bone pathophysiology, novel research on vitamin D indicates its fundamental involvement in a wide range of disease processes through its multiple systemic effects, including but not limited to metabolic, cardiovascular, anti-inflammatory, antineoplastic, antioxidant, neuroprotective, and immune actions. Recent work has yielded important mechanistic insights into the functions of vitamin D in mediating immunity. The present work sheds light on the metabolism and immune response mechanisms of vitamin D. Current review is based on a thorough search of the available relevant research findings of the metabolic transformations of vitamin D and the molecular basis of its role in immunity. Apart from its classical mechanistic control of mineral homeostasis, vitamin D has immunomodulatory effects through various mechanisms at both systemic and cellular levels. Disruption of vitamin D reliant molecular pathways in the regulation of immune response can potentially result in the development and/or progression of autoimmune and infective processes. [GMJ.2021;10:e2097]